The Word of the Body: Depictions of Positive Body Image In Philippine Young Adult Literature - Lee, Gabriela (Philippine Humanities Review; Vol 18 No 1 (2016), 2017)
The relationship between body image and identity is one of the hallmarks of young adult literature. Despite the advances made by various feminist movements, “[G]irls’ lives are still adversely affected by social pressure to adhere to an ideal standard of beauty,” says Beth Younger. This obsession with weight and appearance is a heady mixture of information overload, media portrayal, and an overall propensity for obesity in the past decades due to a number of complicating factors: food production, environmental factors, epigenetic research, and changes in lifestyles. Young adult or YA stories are also part of this continuous portrayal of female bodies as either acceptable or marginal, or even reversing our notions of either concept. In the Philippines, these stories feature female protagonists who consider their appearances, though not necessarily their weight and body shape and size, important enough that the text considers and acknowledges their appearances as part of their struggle to be accepted within certain social spheres. This essay is concerned with the positive portrayal of the fat female body in young adult literature and how it becomes a subversive body, since it performs its pleasures for the self, and not for others. Keywords: young adult literature, body image, fatness